Handycrafts from Corncob and Glyserol Plasticizer - Firra Rosariawari; Novirina Hendrasarie; Tiara Mohamad Mirwan (Future Science)
Management and processing of organic solid waste are simpler than inorganic solid waste. Organic solid waste was more easily decomposed if it was disposed of or buried in the soil. There was no area for the community to be heaped up the organic solid waste. Moreover, the water level is relatively shallow, making it possible for organic waste to mix with groundwater. Corn cobs were an organic solid waste that was mostly produced by the seller of roasted corn or boiled corn on the side of the road. This corncob waste has a contribution to the increase in rubbish in solid waste disposal. For this reason, the use of corn cobs was necessary. This corncob waste can be used as handicrafts to replace handicrafts made from plastic. The community, especially housewives, has the potential to innovate in making handicrafts. It's just that it requires supportive technology for creativity. The results of this community service activity were several handicrafts made from corn cobs that have been processed and added with glycerol as a plasticizer. The method of reusing corncob waste into handicrafts has contributed to reducing corncob waste by corn sellers on the roadside. This community service activity in addition to increasing the creativity of housewives, also indirectly reduces the corn cobs heap in solid waste disposal.